COVID-19 and Women's Health: A Low- and Middle-Income Country Perspective - Premji, Shahirose Sadrudin; Shaikh, Kiran; Lalani, Sharifa; Yim, Ilona S.; Moore, Sarah; Ali, Naureen Akber; Aijaz, Saher; Letourneau, Nicole (Frontiers in Global Women's Health, 2020)
Corona Virus Disease (COVID-19), a contagious disease, is a global pandemic affecting the lives and health of individuals across borders, genders and races. Much of what is known about the effects of disease outbreaks on women’s health in particular, is based on studies conducted in high-income countries. The evolving evidence suggests that COVID-19 has a profound negative impact on the perinatal mental health of women. It is also clear that global pandemics such as COVID-19 disproportionately affect the less affluent, including individuals living in low- and middle-income countries. The purpose of this review is to summarize and critically discuss extant knowledge on COVID-19 as it relates to the perinatal health of women in low and middle-income countries, using Pakistan as a case example. We specifically highlight the effects on perinatal mental health, preterm birth, and timing of the COVID-19 exposure. Our review suggests that it is essential to consider the effects of COVID-19 within this cultural context and that findings from high-income countries do not necessarily translate to the situation in low and middle-income countries.